Non dimenticarsi di Proust Declinazioni di un mito nella cultura moderna - Dolfi, Anna (Moderna/Comparata, 2014)
On the one hand le côté de Guermantes and on the other that of chez Swann... Few places like Illiers-Combray offer the tangible measure of a myth that has involved not only readers and writers, but also those who have reflected on the meaning and structures of modern fiction. As the great criticism of the 20th century and the most innovative reflections on the method would not be conceivable without the Recherche. Auerbach, Curtius, Spitzer, Poulet, Jauss, Deleuze, Richard, Genette, Barthes..., as well as Solmi, Debenedetti, Contini, and Macchia in Italy, measured themselves with essays and/or memorable books, while Caproni, Fortini, Ginzsburg, Raboni... tried themselves with translation. In short, the seduction of a work with a very dense intertextuality and variety of registers still resides, not only in the ability to talk about the history and culture of the West, offering the grandiose fresco of a universe in decline, but in the possibility of inserting itself on many levels (including that of meta-literature, non-fiction) as an obligatory point of passage. Thus contributing to create a world parallel to the real one, which is now populated by its doubles: cities, cathedrals, feelings, emotions, words intermittences... From the field of fiction to that, induced, of narratology, no doubt that Proust has changed our life, the perception of the world, and the way of looking at objects, and of reading books and things. The collection that is proposed here, designed and curated by Anna Dolfi, gives a broad and evocative testimony, offering itself as an essential object of study on the traces of the unforgettable, unseizable Marcel.